Impact of psycho-educational interventions on patients undergoing Coronary Artery Bypass Grafting Surgery - Shahpar Bagheri; Zahra Dadashpouromrani; Giti Setoodeh; Zahra Hadian Shirazi; Azadeh Amiri; Rozhan Ghobadimoghaddam (Journal of Cardiothoracic Surgery)
Abstract Background Postoperative period of Coronary Artery Bypass Grafting can be challenging, with physical and psychological problems and symptoms. We conducted this study to explore the effect of a psycho-educational intervention on anxiety, pain and physiological parameters among Coronary Artery Bypass Grafting surgery patients. Methods A randomized clinical trial design included one experimental and control group. Data were collected from 56 candidates for coronary artery bypass surgery (n = 28) in the intervention and (n = 28) in the usual care groups. Settings were the cardiac centers of the three teaching, specialty, and subspecialty Nemazee, Faghihi, and Al-Zahra hospitals affiliated with Shiraz University of Medical Sciences (SUMS). The data were collected using a demographic information form, the Short-Form McGill Pain Questionnaire, the Spielberger State-Trait Anxiety Inventory, and the physiological parameters form (systolic and diastolic blood pressure, heart rate, respiratory rate, and peripheral oxygen saturation). Psycho-educational interventions were performed individually through face-to-face sessions. All tests were two-tailed, and the statistical level was considered 0.05. Results The mean scores of state anxiety and pain decreased significantly after the intervention (p < 0.05). Also, psycho-educational interventions affected peripheral oxygen saturation percentage, and breathing rate mean scores (P < 0.05). But, they did not affect the blood pressure and pulse rate (P > 0.05). At the same time, there was no significant difference in the control group. Conclusion This study indicated that the pre-operative psycho-educational interventions facilitated intrapersonal caring, reduce state anxiety, relieve pain and stabilize physiological parameters such as peripheral oxygen saturation percentage and breathing rate after surgery among Coronary Artery Bypass Grafting surgery patients. Hence, this intervention is recommended for developing care programs in same population. Trial registration https://www.irct.ir/trial/55652 : IRCT20090908002432N8 (2021-09-17).